Fundamental of Entrepreneurship ENT300 : Case study on Petronas Serian / Muhammad Amin Azman ... [et al.] - Azman, Muhammad Amin; Minggu, Mohamad Gifari; Abdul Hamid, Muhammad Iqhmal; Abdul Karim, Aeman Harris; Azrin, Aiman (2019)
A case study is an analysis of a real life situation where the problems faced by the chosen company must be solved. In our case study, we have chosen PS SERIAN to be observed. This a petrol station owned by a Sarawakian businessman named Abdul Hamid. Mr. Abdul Hamid is currently in his early 50s and has been managing this business by himself. This petrol station has been established since 2015 and it is located in Jalan Lintang, Serian. One of the reason Mr. Abdul Hamid has chosen this particular location to start his business due to this are is the at the heart of Serian and one of the developing area is Sarawak effected by the opening of the Pen Borneo Highway. There are plenty of people in serian, especially construction workers and people that live in the area that needed their tank fill. These people had made the business owner convinced that his petrol station will be a good inveatment of his business. During the process of our case study, we have doing some reserch of this particular petrol station . One of the thing that we noticed is that Mr. Abdul Hamid have made his job quite efficient that he solve all the problems that may cause his business to be bad. This is because of his 25 years of experience that make him good at his field of work. Before that he faces some problem on how to motivate the worker to be more efficient and how to attract customer.